Difficult Internal Jugular Central Venous Cannulation Using J-Tip Guidewire with Indwelling Peripherally Inserted Central Venous Catheters - Preeti Anand; Minal Joshi; Khaja Ahmed; Joel Yarmush (Case Reports in Anesthesiology)
Central venous cannulation is a commonly performed procedure while managing critically ill patients; increasingly we encounter patients with indwelling wires or devices, like pacemakers, implantable cardioverter defibrillator devices, and peripherally inserted central venous catheters which complicate insertion of central venous catheters further. We present two cases where use of standard J-tip guidewire may have exacerbated the difficulty associated with internal jugular cannulation in presence of peripherally inserted central venous catheters. Recognition and avoidance of possible complications are crucial, and we discuss complexity posed by indwelling peripherally inserted central venous catheters and possible solutions.